Regulation of Ant Foraging: A Review of the Role of Information Use and Personality - Kolay, Swetashree; Boulay, Raphaël; d’Ettorre, Patrizia (Frontiers in Psychology, 2020)
Animals live in heterogeneous environments where food resources are transient and have to be exploited rapidly. Ants show a wide range of foraging strategies and this activity is tightly regulated irrespective of the mode of recruitment used. Individual foragers base their decision to forage on information received from nestmates (social information). Transmission of information can be in the form of direct physical interactions such as antennation or indirect exchange of information such as laying of pheromone trails. Foragers also rely on information from their internal states or experience (personal information). The interaction between these two sources of information gives rise to plasticity in foraging behaviour. Recent studies have examined the role of personality (consistent inter-individual variation in behavioural traits) during ant foraging. Since colonies differ from each other in the distribution of personalities of their members, colonies may consistently differ in behavioural traits, giving rise to colony level personality. However, the interaction between information use and personality, especially at the individual level, remains unexplored. Here, we briefly summarize the literature on the effect of social and personal information on the regulation of ant foraging and the effect of personality on this behaviour. We point out that a more focused examination of the interplay between personality and information use will help us understand how behavioural plasticity in the context of foraging in is shaped at the colony and individual levels.